PEMANFAATAN STASIUN TV LOKAL DI MAKASSAR UNTUK IKLAN KAMPANYE CALON ANGGOTA LEGISLATIF 2019 - Muannas Muannas; Muhammad Mansyur (Jurnal Dakwah Tabligh, 2019)
Popularity becomes crucial for politicians in the direct elections event. High popularity is the capital to achieve electability. Popularity requires massive political work, including the use of media, one of which is television. Television has the advantage of being able to present messages in the form of audio-visual so that it gives a big influence. This study aims to examine the use of television stations for campaign advertisements for legislative candidates in the 2019 elections. The television stations that are in focus are the two local television stations in Makassar, Fajar TV and Celebes TV. This type of research is qualitative with descriptive methods. The informant is a candidate who has experience as a TV broadcaster. The study findings were astounding, where the candidates recognized the greatness and influence of television, but instead did not use it to hoist its popularity. Legislative candidates turn to social media.